The Effects of Airfoil Thickness on Dynamic Stall Characteristics of High‐Solidity Vertical Axis Wind Turbines. Issue 6 (5th May 2021) - Bangga, Galih; Hutani, Surya; Heramarwan, Henidya
Abstract: The flow physics of high solidity vertical axis wind turbines (VAWTs) is influenced by the dynamic stall effects. The present study is aimed at investigating the effects of airfoil thickness on the unsteady characteristics of high solidity VAWTs. Seven different national advisory committee for aeronautics (NACA) airfoils (0008, 0012, 0018, 0021, 0025, 0030, 0040) are investigated. A high fidelity computational fluid dynamics (CFD) approach is used to examine the load and flow characteristics in detail. Before the study is undertaken, the CFD simulation is validated with experimental data as well as large eddy simulation results with sound agreement. The investigation demonstrates that increasing the airfoil thickness is actually beneficial not only for suppressing the dynamic stall effects but also to improve the performance of high solidity turbines. Interestingly this is accompanied by a slight reduction in thrust component. The strength and radius of the dynamic stall vortex decrease with increasing airfoil thickness. The airfoil thickness strongly influences the pressure distributions during dynamic stall process, which is driven by the suction peak near the leading edge. The knowledge gained might be used by blade engineers for designing future turbines and for improving the accuracy of engineering models. Abstract : Airfoil thickness is responsible for the dynamic behavior of the vortex on rotating vertical axis wind turbine blades. In this study, high fidelity computational fluid dynamics computations are employed to investigate and to quantify this phenomenon in detail. The results can be used to determine the suitable airfoil thickness for blade design purpose.